MIMO-OFDM Imaging Using Shared Time and Bandwidth - Mehmet Yazgan; Huseyin Arslan; Stavros Vakalis (IEEE Open Journal of the Communications Society, 2025)
Multiple-input multiple-output (MIMO) orthogonal frequency-division multiplexing (OFDM) radar imaging has emerged as a promising approach for high-resolution environmental sensing, particularly in spectrally congested wireless environments. This paper presents a novel MIMO-OFDM imaging framework that enables simultaneous transmission from multiple antennas without relying on conventional time-division multiplexing (TDM) or frequency-division multiplexing (FDM) techniques. The proposed method preserves the standard OFDM communication waveform, eliminating the need for additional interference mitigation strategies. Two transmit (Tx) and two receive (Rx) antennas operate within a 400 MHz bandwidth at carrier frequencies of 2.4 GHz and 2.415 GHz, each transmitting independently modulated quadrature amplitude modulation (QAM) symbols. Theoretical analysis, simulations, and experimental measurements demonstrate that high-fidelity object reconstruction is achieved despite overlapping spectral and temporal resources. The results validate the feasibility of this approach for efficient spectral and temporal resource utilization in wireless sensing applications, making it favorable for existing and upcoming wireless applications with a massive number of active sensing devices, such as joint-radar and communications (JRC) and the Internet of Everything (IoE).